Influence of Certain Cations on Activity of Succinyl CoA Synthetase From Tobacco - Bush, Lowell P. (1969)
Succinyl CoA synthetase from Nicotiana tabacum exhibited a requirement for univalent and divalent cations. Mn(2+) replaced Mg(2+) in the assay medium and Co(2+) and Ca(2+) partially replaced Mg(2+). Addition of Zn(2+) resulted in no enzyme activity. The enzyme was activated by univalent cations K(+), Rb(+), NH(4)(+), and Na(+); Li(+) showed little or no activation. Maximum enzyme activity varied significantly with potassium salts of different anions. Greatest activation was obtained with K(3)PO(4) and, respectively, KCl, KNO(3), K(2)SO(4) and KF exhibited steadily decreasing enzyme activation.